Arginine Catabolic Mobile Elements in Livestock-Associated Methicillin-Resistant Staphylococcal Isolates From Bovine Mastitic Milk in China - Tong, Chao; Wu, Zhaowei; Zhao, Xin; Xue, Huping (Frontiers in Microbiology, 2018)
The arginine catabolic mobile element (ACME) facilitates colonization of staphylococci on skin and mucous membranes by improving their tolerances to polyamines and acidic conditions. ACME is inserted in tandem with the SCCmec element and S. epidermidis has been proposed to be a reservoir of ACME for other staphylococci. In this study, we investigated the existence of ACME in 146 staphylococcal isolates from mastitic milk and found 21 of them carried ACME. Almost half of the investigated S. epidermidis isolates contained the element. The whole genome of a S. epidermidis strain Y24 with ACME was further sequenced and the ACME-SCCmec composite island was assembled. This composite island is 81.3 kb long and consisted of 77 ORFs including a methicillin resistance gene mecA, a type II’ ACME gene cluster, a virulence gene pls and eight heavy metal tolerance genes. Wide existence of ACME in livestock-associated staphylococci from this study and a potential risk of spreading ACME among different staphylococcal species warrant close monitoring and further studies.